The Market Formation of Value and Preferences: An Empirical Study of Electronic Word-of-Mouth in the Indonesia E-Commerce for Cosmetic Product - Romli, Zainur (Universitas Pendidikan Ganesha, 2024)
This study aims to investigate the influence and impact of Electronic Word-of-Mouth (E-WOM) on the formation of product value and consumer purchase preferences in the cosmetic market context, referring to signal quality. The analysis was conducted within the dynamic digital market context, where product value is formed exogenously and is filled with uncertainty. This condition underscores the importance of reputation management and online consumer interaction for cosmetic companies in optimizing their products in the ever-evolving digital market arena. Unlike previous studies that explored product value formation conventionally, this research explores market interactions directly within the digital marketplace. This study employs a digital research method utilizing web scraping techniques with Python algorithms. The results reveal that the product value formed from E-WOM on the Bukalapak online marketplace for Kahf Face Wash products predominantly responds to signal quality from functional aspects. Additionally, E-WOM extends into the domain of social value. The analysis highlights that consumers evaluate this product comprehensively as an essential skincare necessity and as part of the entire market activation system, from packaging to seller service.